Peningkatan Literasi Donor Darah dan Pencegahan Anemia Berbasis Edukasi Partisipatif pada Remaja melalui Keterlibatan Mahasiswa Universitas Dr. Soetomo - Sasi Widuri; Yustisia Amalia; Cityta Putri Kwarta; Lentera Afrida Kusumawardani; Wiwid Samsulhadi; Putu Ayu Dhana Reswari (Health Care : Journal of Community Service, 2025)
The issues of blood availability and the high prevalence of anemia among adolescents remain major public health challenges in Indonesia. Low health literacy, misconceptions about blood donation, and unbalanced dietary patterns highlight the need for systematic and sustainable educational interventions. This community service activity aimed to improve adolescents’ knowledge, attitudes, and behavioral readiness related to blood donation and anemia prevention through participatory education involving students of Universitas Dr. Soetomo as agents of change. The program was conducted offline through interactive lectures, dialogic discussions, simulations, and evaluations using pre-test and post-test methods. A total of 50 participants were involved, consisting of 15 males and 35 females. The results demonstrated an increase in the average knowledge scores from a moderate category in the pre-test to a high category in the post-test, accompanied by more positive attitudes toward blood donation and increased awareness of nutrition and iron supplementation. These findings indicate that student-based participatory health education is effective in enhancing adolescent health literacy. This community service initiative is important as a model of community empowerment oriented toward health behavior change and the strengthening of the role of higher education institutions in public health development.